2011
DOI: 10.1002/elsc.201000068
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic devices and true‐color sensor as platform for glucose oxidase and laccase assays

Abstract: The commonly used assay for measuring glucose oxidase (GOx) and laccase (Lac) activity, based on spectrophotometric test using 2,2′‐azinobis‐(3‐ethylbenzothiazoline‐6‐sulfonic acid) (ABTS), has been adapted to measure these enzyme activities via microfluidic devices. The effects of flow rate and concentration of substrates were examined. The developed assays allowed analyzing GOx and Lac activities in the range of 0.8–8.0 Unit (0.1–1.0 mg/mL) and 0.9–17.7 Unit (0.1–2.0 mg/mL), respectively. Moreover, repeatabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…The length of the mixing channel and the flow rate in it determine the reaction time which has strong influence on signal strength, linear range and sensitivity of the measurement (Demirkol et al, 2011;Ohnishi et al, 2010;Songjaroen et al, 2009;Wu et al, 2007). For example, for absorbance measurements an optimum reaction time for the enzymatic reaction can be found that gives the strongest color development and hence the highest sensitivity (Wu et al, 2007).…”
Section: Mixingmentioning
confidence: 99%
“…The length of the mixing channel and the flow rate in it determine the reaction time which has strong influence on signal strength, linear range and sensitivity of the measurement (Demirkol et al, 2011;Ohnishi et al, 2010;Songjaroen et al, 2009;Wu et al, 2007). For example, for absorbance measurements an optimum reaction time for the enzymatic reaction can be found that gives the strongest color development and hence the highest sensitivity (Wu et al, 2007).…”
Section: Mixingmentioning
confidence: 99%
“…Considering the industrial applicability, a low concentration of substrate may be a major restriction for the enzymatic reaction [27,28]. To test the feasibility of ArEH in the production of chiral epichlorohydrin and its potential for industrial application, the effect of the racemic epichlorohydrin concentration on the resolution was studied at various concentrations ranging from 25.6 to 384 mM ( Table 1).…”
Section: Effect Of the Substrate Concentration On The Reactionmentioning
confidence: 99%
“…The integration of enzyme assays in microfluidic systems has been reported with the aim to quantify specific analytes in food and medical samples (Atalay et al 2009a;Laiwattanapaisal et al 2009;Vergauwe et al 2011), to screen and characterize enzyme inhibitors (Hadd et al 1997;Boer et al 2005) and to measure enzyme activity (Clark et al 2009;Demirkol et al 2011). With respect to the implementation of enzyme assays in microfluidic systems, differentiation is made between heterogeneous and homogeneous systems.…”
Section: Introductionmentioning
confidence: 98%
“…On the other hand, enzymatic assays are also executed on microfluidic platforms driven by pressure micropumps. For instance, Demirkol et al (2011) have successfully developed a simple method to determine the enzyme activities of glucose oxidase and laccase on microfluidic chip.…”
Section: Introductionmentioning
confidence: 99%